1977
DOI: 10.1007/bf00463193
|View full text |Cite
|
Sign up to set email alerts
|

Liability of ultrasound in maxillary sinus disease

Abstract: For the first time liability of of ultrasonography in diagnosing paranasal sinus disease was controlled in 256 patients with acute maxillary sinusitis as compared to irrigation findings and in 150 patients with persistent maxillary sinus disease using x-rays, sinoscopy and sinumanometry as controls. Confidence in diagnosing the presence of discharge ranges up 90%. In cases of total opacity of the sinus, ultrasonography helps differentiating mucosal swelling, tumor and discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

1979
1979
1999
1999

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(12 citation statements)
references
References 5 publications
0
10
0
2
Order By: Relevance
“…For chronic sinusitis, a statistically significant correlation between ultrasound and X-ray diagnoses of mucosal thickening and fluid retention, was reported by Mann et al in their study in 1977 (10). The correlation between radiographic lateral mucosal thickening and A-US results was also statistically significant in the group of chronic sinusitis patients studied by Revonta (1980) (14).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…For chronic sinusitis, a statistically significant correlation between ultrasound and X-ray diagnoses of mucosal thickening and fluid retention, was reported by Mann et al in their study in 1977 (10). The correlation between radiographic lateral mucosal thickening and A-US results was also statistically significant in the group of chronic sinusitis patients studied by Revonta (1980) (14).…”
Section: Introductionmentioning
confidence: 61%
“…A-US has proved to be a clinically reliable detec-tor of fluid retention in patients suffering from acute maxillary sinusitis in most studies. Mann et al (1977) reported a confidence of 90.2% between A-US and puncture findings in a series of 256 acute suspected maxillary sinusitis patients (10). Revonta (1979) found that fluid retention in the maxillary sinus could be even more reliably diagnosed with A-US in children (96%) (11).…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of this diagnostic procedure have been described several times (1)(2)(3)(4). Broader application was limited not only due to the subtle handling and difficulties in individual equipment adjustments but also to a lack of formal training in the interpretation of various echograms.…”
Section: Uliyilmentioning
confidence: 99%
“…The most common cause of a false negative ultrasonic finding was the small amount of secretion, which could not carry the ultrasonic beam to a perpendicular bony back wall (10). False positive indications of sinus fluid were mostly caused by mucosal thickening or polypslcysts, which cannot be detected with the same high degree of confidence as fluid either by using the one-dimensional A-mode or the two-dimensional B-mode (8,10).…”
mentioning
confidence: 99%